Architecture and Interior Design as a Reflection of Identity and Social Class: A Case Study of Nyai Ontosoroh’s House in Bumi Manusia - Ari Darmastuti, Putu; Yuni Diantari, Ni Kadek; Udiyana Wasista, I Putu (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
Architecture and interior design not only represent aesthetic and functional aspects, but also act as tools for constructing identity, power, and social class. This study analyzes Nyai Ontosoroh's house in Pramoedya Ananta Toer's novel Bumi Manusia as a representation of social class ambiguity and spatial symbolism in the colonial context of the Dutch East Indies. Through an interdisciplinary approach between literary studies, architecture, and postcolonial theory, this paper explores how the physical form of the house, the division of space, and interior elements become a means of resistance against colonial and patriarchal social structures. Nyai's Indisch-style house, complete with a garden, a carpeted attic, a spacious living room, and a luxurious bathroom, not only reflects high social status, but also becomes an arena for negotiating gender and racial identities. The results of the analysis show that the domestic space in this novel is a